Perception of students on provisions provided to cycle three students with mental illnesses (anxiety disorder and depression (in public schools in the United Arab Emirates: an expletory study - Jawaher, Alkaabi (2022)
Anxiety disorders and depression are the most common mental disorders among adolescents. It is well-established that both anxiety disorder and depression negatively impact adolescents’ academic performance, social life, and their general well-being. This study aimed to explore services provided for cycle three students (14-18 yo) in public schools in the United Arab Emirates in terms of mental health and what could be further offered to help in improving students’ mental well-being. Data was collected using a qualitative method in the form of Semi-structured interviews were conducted with current and former students in public schools to explore their perception of anxiety disorder and depression, to assess what is currently on offer for students who are dealing with anxiety disorder and depression, and to discuss what could public schools further offer to Improve their mental health. The results indicated that there is little to no systematic services offered to students with anxiety disorder and depression. Furthermore, the results also showed a few systematic measures that could be taken by public schools to improve students’ wellbeing such as a mental health professional in schools, longer breaks during the school day, allocated times for solitary activities, and more physical education classes.